A Review of Aspirin-exacerbated Respiratory Diseases and Immunological Efficacy of Aspirin Desensitization - Hossein Esmaeilzadeh; Maryam Zare; Soheila Alyasin; Hesamedin Nabavizadeh; Negar Mortazavi; Zahra Kanannejad (Iranian Journal of Allergy, Asthma and Immunology, 2022)
Aspirin-exacerbated respiratory disease (AERD) is a chronic inflammatory disease. It is defined by asthma, chronic rhinosinusitis with nasal polyposis, and a hypersensitivity reaction to aspirin or nonsteroidal anti-inﬂammatory drugs. Aspirin desensitization (AD) has been confirmed as an effective treatment to control AERD inflammation through the modulation of immune responses. We aimed to review AERD with an overview of the epidemiology, pathophysiology, and treatment. We also discussed the effect of AD on immunological markers involved in AERD pathogenesis. A search of electronic databases on AERD was performed. We included five randomized clinical trials (RCTs) on AD. We also searched databases for recent studies that investigated the effect of AD on the immunological mechanisms of AERD. RCTs have demonstrated the therapeutic effectiveness of AD on the patients’ quality of life, asthma symptom score, inhaled and oral steroid use, forced expiratory volume in 1 sec (FEV1), and inflammatory mediators. The clinical benefits of AD can occur though the regulation of innate and adaptive immune responses that are involved in the pathogenesis of AERD. In addition to the valuable effects of AD in RCTs, some side effects such as gastrointestinal bleeding, asthma exacerbation, or rash have been reported that should be considered for reaching an optimal protocol for AD.